Gemini AI Chatbot Improves Academic Achievement and Motivation of 11th Grade High School Students - Suhananto; Pujiriyanto (Universitas Pendidikan Ganesha, 2025)
The decline in students’ achievement and learning motivation is influenced by several factors, including boredom caused by monotonous teaching methods and difficulties in adapting to face-to-face learning after online learning. This study aimed to analyze the effect of the Gemini AI Chatbot on the academic achievement and motivation of 11th-grade high school students. The research employed a quasi-experimental design. The population consisted of 216 11th-grade students, with a sample of 71 students selected using cluster random sampling. Data were collected through questionnaires and tests, with research instruments consisting of a questionnaire sheet and test items. Data analysis used quantitative descriptive analysis and inferential statistics. The MANOVA and independent t-test results showed a significance value of 0.000 (Sig. 2-tailed) < 0.05 across all aspects of learning achievement, with Partial Eta Squared values ranging from 0.10 to 0.268, indicating an effect on student performance. The F value was 123.377 with Sig. 0.000 and an effect size of 0.744, indicating that the AI Chatbot Gemini had a significant effect on motivation. The Sig. value of 0.000 on all multivariate test indicators (Pillai’s Trace, Wilks’ Lambda, Hotelling’s Trace, and Roy’s Largest Root) and an observed power of 1.000 demonstrated a significant influence on both academic achievement and motivation. It can be concluded that the Gemini AI Chatbot effectively enhances the academic achievement and motivation of 11th-grade high school students. The study implies that the Gemini AI Chatbot has a positive impact on students’ academic performance and learning motivation.